2011
DOI: 10.1007/s00127-011-0386-4
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment among patients with newly diagnosed first-episode psychosis: prevalence and clinical correlates in a US sample

Abstract: The remarkably high rate of unemployment in this young, first-episode sample, and the evidence of associations between unemployment, greater symptomatology, and poorer functioning, argue for further research and development on supported employment programs for such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 31 publications
1
46
1
2
Order By: Relevance
“…Thus, the independence-competence factor was significantly higher in participants with jobs compared to those who were unemployed. Our results therefore tie in with those stating that measurements of social functioning are stronger in this respect than those which assess symptomatology exclusively (Giugiario et al, 2012;Kilian et al, 2012;McGurk & Mueser, 2004;Ramsay, Stewart & Compton, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the independence-competence factor was significantly higher in participants with jobs compared to those who were unemployed. Our results therefore tie in with those stating that measurements of social functioning are stronger in this respect than those which assess symptomatology exclusively (Giugiario et al, 2012;Kilian et al, 2012;McGurk & Mueser, 2004;Ramsay, Stewart & Compton, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…It is essential to design effective educational programs to compensate for their lack of academic experience. In turn, the fact that the variable "sex" (woman) enters the equation which predicts ordinary employment must be related to the lower neuropsychological deficit, better progression and less negative symptomatology which seems to affect women with schizophrenia (Gogos et al, 2010;Ramsay et al, 2012), it may also be related to the specific employment opportunities found in Andalusia. Similar correlates between sex (being women), high educational level and competitive employment have been found in previous studies (Waghorn, Saha & McGrath, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although not shown, it is also noteworthy that the mean age at hospitalization was 23.1 ± 4.7 years (range: 18–39) and 98 of the participants (89.9%) were African American. Descriptions of other social variables are given elsewhere, including in‐depth information on high rates of high school dropout (44.0%), 32 prior incarceration (57.8%) 33 and unemployment prior to hospitalization (65.0%) 34 . The majority of participants (82, 75.2%) were admitted to an inpatient unit with an average length of stay of about 10 days, with smaller numbers admitted to a crisis stabilization unit in the same hospital with an average length of stay of about 6 days (17, 15.6%), and a similar crisis stabilization unit in a neighbouring suburban county (10, 9.2%).…”
Section: Methodsmentioning
confidence: 99%
“…Recent estimates of unemployment at presentation are between 59 [7] and 65% [8], and this is associated with poor global functioning [8]. Recent estimates of unemployment at presentation are between 59 [7] and 65% [8], and this is associated with poor global functioning [8].…”
Section: Psychosocial Outcome In First-episode Psychosismentioning
confidence: 99%